Difference in Frequency and Distribution of Nodal Metastases Between Intermediate and High Risk Prostate Cancer Patients: Results of a Superextended Pelvic Lymph Node Dissection - Roscigno, Marco; Nicolai, Maria; La Croce, Giovanni; Pellucchi, Federico; Scarcello, Manuela; Saccà, Antonino; Angiolilli, Diego; Chinaglia, Daniela; Da Pozzo, Luigi F. (Frontiers in Surgery, 2018)
Objectives: To evaluate the frequency and distribution of pelvic nodes metastases, in intermediate-high risk prostate cancer (PCa) patients (pts), who underwent open radical prostatectomy (ORP) and superextended pelvic lymph node dissection (sePLND). Patients and Methods: We retrospectively evaluated 630 consecutive pts with clinically localized, intermediate-high risk PCa, treated with ORP and sePLND from 2009 to 2016 at a single institution. The sePLND always removed all nodal/fibro-fatty tissue of the internal iliac, external iliac, obturator, common iliac, and presacral regions. Results: Positive lymph nodes (LN+) were found in 133 pts (21.1%). The median number of removed nodes and LN+ was 25 and 1, respectively. LN+ were found in 64 (48.1%), 58 (43.6%), 53 (39.8%), 16 (12%), and 20 (15%) pts and were present as a single site in 27 (20.3%), 22 (16.5%), 20 (15%), 0, and 6 (4.5%) cases in the internal iliac, external iliac, obturator, common iliac, and presacral chain, respectively. An ePLND would have correctly staged 127 (95%) pts but removed all LN+ in only 97 (73%) pts. Presacral nodes harbored LN+ in 20 patients. Among them, 18 were high-risk patients. Moreover, all but 1 pts with common iliac LN+ were in high risk group. Conclusions: These results suggest that removal of presacral and common iliac nodes could be omitted in intermediate risk pts. However, a PLND limited to external iliac, obturator, and internal iliac region may be adequate for nodal staging purpose, but not enough accurate if we aim to remove all possible site of LN+ in high risk pts.